1992
DOI: 10.1002/hep.1840160102
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial Pressure Monitoring and Liver Transplantation for Fulminant Hepatic Failure

Abstract: Cerebral edema and intracranial hypertension, commonly present in fulminant hepatic failure, may lead to brainstem herniation and limit the survival of comatose patients awaiting liver transplantation before a donor organ becomes available. Also, they are likely responsible for postoperative neurological morbidity and mortality. Although intracranial pressure monitoring has been proposed to aid clinical decision making in this setting, its use in the prevention of brainstem herniation preoperatively, in the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
95
0
4

Year Published

1993
1993
2014
2014

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 252 publications
(101 citation statements)
references
References 18 publications
2
95
0
4
Order By: Relevance
“…Previous studies of ICP monitoring in patients with liver failure suggested that the greatest benefit of these devices occurs intraoperatively, during transplantation, when wide volume swings increase the risk for cerebral edema. 25 This observation, along with the decreased occurrence of anasarca with rFVIIa use, may explain the infrequent need for intervention to treat intracranial hypertension in our patients treated with rFVIIa. Unfortunately, because we were unable to place ICP monitors in most of the control (plasma-treated) patients, we were unable to directly compare the incidence of intracranial hypertension in the two groups.…”
Section: Discussionmentioning
confidence: 74%
“…Previous studies of ICP monitoring in patients with liver failure suggested that the greatest benefit of these devices occurs intraoperatively, during transplantation, when wide volume swings increase the risk for cerebral edema. 25 This observation, along with the decreased occurrence of anasarca with rFVIIa use, may explain the infrequent need for intervention to treat intracranial hypertension in our patients treated with rFVIIa. Unfortunately, because we were unable to place ICP monitors in most of the control (plasma-treated) patients, we were unable to directly compare the incidence of intracranial hypertension in the two groups.…”
Section: Discussionmentioning
confidence: 74%
“…The sample size was based on previously reported data. 9 A difference of 10 mm Hg in mean intracranial pressure (ICP) between groups was anticipated, based on previous anecdotal experience using hypertonic saline to treat patients with ALF. This expectation, together with an ␣ value of 0.05 and a ␤ value of 0.2, yielded a target sample size of 29 patients.…”
Section: Methodsmentioning
confidence: 99%
“…Loss of oculovestibular reflexes and depressed cerebral perfusion pressures that cannot be easily controlled are almost invariably associated with irreversible brain stem damage. 140 Furthermore, patients who require continuous pressor support to maintain an adequate blood pressure cannot tolerate the rigors of major surgery. The APACHE III criteria may be a useful adjunct to clinical judgment in identifying these patients.…”
Section: Recommendationsmentioning
confidence: 99%